Pengaruh Budaya Organisasi, Gaya Kepemimpinan, Dan Motivasi Terhadap Kinerja Karyawan PT Coca-Cola Distribution Surakarta - Anggraeni, Puspitaningdyah, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
The research aims to examine and analyze the influence of organizational culture leadership style and motivation toward performance of employee in PT Coca-Cola Distribution Surakarta. Data collected through distribution of questionnaires and it is implemented to PT Coca-Cola Distribution Surakarta's 74 employees. Analysis of data in this research using the help of SPSS version 17. Analysis of method is double linear regression analysis to verify and to prove the research hypothesis. Analysis result demonstrates that organizational culture, leadership, motivation style (statistically) have a siignificant influence toward employee performance. Keywords: organizational culture, leadership style, motivation, employee performance.